Advancements in Understanding and Enhancing Antioxidant-Mediated Sperm Cryopreservation in Small Ruminants: Challenges and Perspectives - Daniel Ionut Berean; Liviu Marian Bogdan; Raluca Cimpean (MDPI AG, 2024)
Cryopreservation poses significant challenges to the preservation of sperm integrity and function, particularly in small ruminants where cryodamage is pronounced. This review explores the molecular mechanisms underlying sperm cryodamage and strategies for improving cryopreservation outcomes, with a focus on the role of antioxidants. Cryopreservation-induced alterations in proteins and RNA transcripts critical for sperm function, including motility, capacitation, fertilization, and embryo development, are discussed. Proteomic, transcriptomic, and epigenomic advancements have provided valuable insights into these mechanisms, offering potential biomarkers for predicting sperm freezability and enhancing cryopreservation strategies. Combining technologies such as mass spectrometry and flow cytometry allows for a comprehensive understanding of molecular and cellular changes induced by the freezing-thawing process. However, challenges remain in optimizing cryoprotectant formulations and antioxidant supplementation to improve post-thaw sperm fertility. Further research is needed to explore a wider range of novel cryoprotectants, antioxidants, and proteins for cryopreservation media, as well as to validate their efficacy in enhancing sperm viability and function. Additionally, investigations into the effects of cryopreservation on RNA transcripts and epigenetic factors in small ruminant species are warranted to advance our understanding of sperm preservation. Overall, this review highlights the importance of antioxidants in mitigating cryodamage and underscores the need for continued research to refine cryopreservation protocols and improve reproductive outcomes in small ruminants.